Association of serum vitamin D levels in Japanese patients with multiple sclerosis. Issue 2 (24th June 2013) - Niino, Masaaki; Fukazawa, Toshiyuki; Miyazaki, Yusei; Minami, Naoya; Tashiro, Jun; Amino, Itaru; Nonaka, Takayuki; Fujiki, Naoto; Doi, Shizuki; Kikuchi, Seiji
Abstract Objective Vitamin D levels are one of the most likely environmental factors related to the development of multiple sclerosis (MS). As vitamin D levels differ between ethnicities, the associated risk of MS also differs. We aimed to determine the associations of serum vitamin D levels in Japanese patients with MS. Methods Serum levels of 25‐hydroxyvitamin D (25[OH]D), 1, 25‐dihydroxyvitamin D (1, 25[OH]2D), and vitamin D‐binding protein (DBP) were measured in 29 patients with relapsing‐remitting (RR) and secondary‐progressive (SP) MS, and in 34 healthy controls. Results The serum levels of 25(OH)D in SPMS patients were significantly decreased compared with those of controls and RRMS patients at remitting phase (7.9 ± 7.2 nM vs 24.2 ± 14.2 nM vs 22.5 ± 13.2 nM, respectively; P < 0.05, P < 0.01, respectively). DBP levels in RRMS and SPMS patients were also decreased compared with controls (419.4 ± 76.2 μg/mL vs 416.7 ± 65.9 μg/mL vs 527.6 ± 149.4 μg/mL, respectively; P < 0.01, P < 0.05, respectively). Furthermore, serum 25(OH)D was found to correlate negatively with disease severity in patients with RRMS in the remitting phase and SPMS using the Expanded Disability Status Scale and the Multiple Sclerosis Severity Score. Conclusions Our results suggest that low 25(OH)D levels are associated with an increased risk of developing SPMS, and a likelihood of developing more severe MS with a worse prognosis in Japanese patients. [Correction added on 2 August 2013, after first online publication: 'serum 25 (OH)D was found to correlate negatively with 1, 25(OH)2D levels in patients' has been corrected to 'serum 25(OH)D was found to correlate negatively with disease severity in patients' in the Results section of the abstract.]